Investigating how river flow regimes impact on river delta salinization through idealized modeling - Matsoukis, Constantinos; Amoudry, Laurent O.; Bricheno, Lucy; Leonardi, Nicoletta (Frontiers in Marine Science, 2023)
Introduction Excessive salinity can harm ecosystems and compromise the various anthropogenic activities that take place in river deltas. The issue of salinization is expected to exacerbate due to natural and/or anthropogenic climate change. Water regulations are required to secure a sufficient water supply in conditions of limited water volume availability. Research is ongoing in seek of the optimum flow distribution establishing longer lasting and fresher conditions in deltas. Methods In this study a three–dimensional (3D) numerical model built for an idealized delta configuration was utilized to investigate how different river discharge annual distributions affect saltwater in deltas. Five simulations were carried out by implementing annual distributions of equal water volume but different shape. Results The results showed that peak flow magnitude, time of occurrence and the length of a hydrograph’s tails can be important parameters affecting stratification, freshwater residence, and renewal times. Hydrographs of small flow range and light tails were the most successful in keeping the delta and its trunk channel fresher for longer periods. Salinity distributions showed a slower response to decreasing rather than increasing river discharges. An increase in the flow rate can result in salinity standards demanded for certain activities (e.g., farming, irrigation etc.) in much shorter times. On the other hand, hydrographs with heavy tails can push the salt intrusion limit further away and be more efficient in mixing the water column. However, they present low freshwater residence and high-water renewal times. Discussion These results provide strong indications that it is possible to improve the freshwater conditions in deltas without seeking for additional water resources but by modifying the water distribution. The main outcomes of this work may be able to support and assist coastal scientists and stakeholders dealing with the management of freshwater resources in river deltas across the world.